Relevance status value model of Index Islamicus on Islamic history and civilizations - Othman, Roslina; Salahuddin, Ashraf Ali (Emerald Group Publishing, 2015)
Sorting the retrieved results from the most relevant to the least relevant is the common option of an Information Retrieval System (IRS). This sorting mechanism or relevance judgment is computed by measuring closeness of query with its documents. The purposes of this study were to measure the relevance status of Index Islamicus, evaluate the semantic correlation between a query and documents, and inquire the basis of its rank.